2014
DOI: 10.1111/bdi.12214
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysfunction in bipolar disorder and suicide risk: is there an association between peripheral corticotropin‐releasing hormone and interleukin‐1β?

Abstract: These results suggest that peripheral mechanisms linking stress hormones and the immune system might be critical patterns involved in suicidal behavior associated with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 47 publications
3
26
1
Order By: Relevance
“…Consistent with the previous studies, it was revealed that in BD, the immune system is chronically activated by microglia, which in turn produces cytokines that render the brain to a vulnerable and unstable state, precipitating mood disturbances [45][46][47]. In fact, higher levels of IL-1β were associated with dysfunction and increased suicide risk in patients with BD [48].…”
Section: Mechanisms Of Neuroinflammationsupporting
confidence: 83%
“…Consistent with the previous studies, it was revealed that in BD, the immune system is chronically activated by microglia, which in turn produces cytokines that render the brain to a vulnerable and unstable state, precipitating mood disturbances [45][46][47]. In fact, higher levels of IL-1β were associated with dysfunction and increased suicide risk in patients with BD [48].…”
Section: Mechanisms Of Neuroinflammationsupporting
confidence: 83%
“…Three out of nine studies found higher levels of IL-1β, but seven found no association with suicidal ideation and behavior in samples of CSF (Martinez et al, 2012) and serum (Monfrim et al, 2014), or with suicide, in postmortem tissue (Pandey et al, 2012). …”
Section: Resultsmentioning
confidence: 98%
“…Two prospective studies (Isung et al, 2012b; Lindqvist et al, 2011) concerned the ability of baseline cytokine levels, among 182 individuals with a history of suicide attempt, to predict 16 subsequent suicides. Seven articles concerned suicidal ideation (Gabbay et al, 2009; Juengst et al, 2014; Karlović et al, 2012; Martinez et al, 2012; Mendlovic et al, 1999; Monfrim et al, 2014; O'Donovan et al, 2013) in 499 research participants: 156 patients with suicidal ideation, 188 patients with no suicidal ideation, and 176 normal controls. See Tables 1-3 for a description of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo blood levels for IL-1β were significantly increased in patients with suicidality, without significant between-study heterogeneity, despite inclusion of subjects with different primary psychiatric diagnoses. One study investigated patients with bipolar disorder with versus without suicidality (28), and two studies investigated patients with MDD with versus without suicidality (14,16). These findings raise the possibility that associations between cytokines and suicidality may be independent of psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 99%